The Administrative Responsibility for the Use in the Name of a Legal Entity of the Words “Stock Exchange”, “Trading System”, “Trade Organizer” - T. V. Golovanova; A. E. Yuritsin (Сибирское юридическое обозрение, 2018)
The article is devoted to topical issues of administrative responsibility, stipulated by the Code of the Russian Federation on Administrative Offenses, for legal entities, for the use in the name and (or) in advertising of the words “stock exchange”, “trading system”, “trade organizer”, as well as words derived from them and word combinations. The authors, analyzing the judicial practice, the opinions of the founders of legal entities brought to administrative responsibility for this offenses, come to the conclusion that these offenses are in most cases committed unintentionally. It is advisable to legislatively exclude the possibility of registration of a legal entity by an authorized federal executive body at the stage of submission of constituent documents in the event that the words “stock exchange”, “trading system”, “trade organizer”, as well as words and phrases derived from them, are included in its name. In addition, the administrative fines provided for such an offense are disproportionate to the gravity of the administrative offense. This fact is confirmed by the absence of a unanimous opinion among judges on the fact of adopting a decision to award a fine to a legal entity in the prevailing legal realities.